2006
DOI: 10.1111/j.1399-0039.2006.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution molecular characterization of the HLA class I and class II in the Tarahumara Amerindian population

Abstract: We describe for the first time the high-resolution profiling of HLA-A, -B, -C, -DRB1, -DQB1 and -DPB1 in a culturally and geographically distinct Mexican ethnic group, the Tarahumaras. The alleles most frequently found by reference strand-mediated conformational analysis in this population were for class I: HLA-A*240201, *020101/09, *0206, *310102, *680102; HLA-B*4002, *1501, *510201, *3501/02/03, *4005, *4801; HLA-Cw*0304, *0801, *0102, *040101; and for class II: HLA-DRB1*080201, *1402, *040701; HLA-DQB1*0402… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 48 publications
(89 reference statements)
1
34
0
Order By: Relevance
“…These findings may indicate that those haplotypes could be frequent in an ancestral group from which both Amerindians and South-East Asians originated from. Amerindian HLA - C /− B blocks observed in the present study, have been also reported, with high frequencies, among Amerindian groups including Zapotecs, Mixe, and Mixtec from Oaxaca State in the southeast of Mexico [16]; Tarahumara from Chihuahua State in the north of Mexico [17]; Native Americans from US [18]; and Yucpa from Venezuela [19]. Genetic admixture estimations were similar to those previously reported data from Mexico City [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings may indicate that those haplotypes could be frequent in an ancestral group from which both Amerindians and South-East Asians originated from. Amerindian HLA - C /− B blocks observed in the present study, have been also reported, with high frequencies, among Amerindian groups including Zapotecs, Mixe, and Mixtec from Oaxaca State in the southeast of Mexico [16]; Tarahumara from Chihuahua State in the north of Mexico [17]; Native Americans from US [18]; and Yucpa from Venezuela [19]. Genetic admixture estimations were similar to those previously reported data from Mexico City [9].…”
Section: Discussionsupporting
confidence: 91%
“…Caucasian component was estimated with a pooled sample (N = 315) consisting of data from southern Portugal [34] and an European population sample from USA [18]; African Nandi from Kenia [59] served as the African parental component (N = 239); a pooled Native American sample (N = 146) was used, which consisted of data from Mixtec of Oaxaca, SE Mexico [16] and Tarahumara from Chihuahua, north of Mexico [17]; finally, Han from southern China data (N = 281) were used to estimate the Asian contribution [60]. Principal Components Analysis (PCA) for 38 populations with HLA-B data available was performed using the IBM SPSS Statistics 19 software ( IBM Corporation, Armonk, NY, USA ) to analyse the distribution of HLA-B alleles in human groups of the proposed ancestries, Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the HLA 36 genes started to be analyzed in many of these groups, KIR genes were still not well characterized. There- 37 fore, they have never been analyzed in a joint context. We thoroughly examined the HLA haplotypes of 38 these populations; for the first time, we are showing the frequencies of the known HLA ligands of most 39 of these populations, which had been separately studied for both KIR and HLA.…”
mentioning
confidence: 98%
“…We chose the isolated Tarahumara Amerindians from North Mexico [18] a s the basal comparison ethnic group, a group whi ch is sharply defined by bot h genetically and a nthropologically c riteria. Al so, this T arahumara group has been shown to have a comparatively low number of KIR genotypes [19].…”
Section: Genetic D Istances a Ccording T O K Ir Frequencies V Ariationmentioning
confidence: 99%